Employment creation and unemployment problems in Ireland in the 1980s - O'Connor, R. (Statistical and Social Inquiry Society of Ireland, 1983)
The purpose of this paper is to look at the development of employment and unemployment patterns in the state in recent years, to consider the numbers which will be coming on the labour market over the coming decade and to determine how we can deal with this inflow, both in the short and long term, within the current national financial constraints. Unfortunately, I have few, if any, original solutions to offer. My purpose is to raise some of the main issues for discussion at the meeting and hope that the informed opinions expressed will generate useful ideas for policy makers.
Read before the Society, 3 March 1983
Keywords: Employment creation; Unemployment, Ireland, 1980s; 314.15